Defective dimerization of FoF1‐ATP synthase secondary to glycation favors mitochondrial energy deficiency in cardiomyocytes during aging. Issue 3 (2nd March 2022) - Bou‐Teen, Diana; Fernandez‐Sanz, Celia; Miro‐Casas, Elisabet; Nichtova, Zuzana; Bonzon‐Kulichenko, Elena; Casós, Kelly; Inserte, Javier; Rodriguez‐Sinovas, Antonio; Benito, Begoña; Sheu, Shey‐Shing; Vázquez, Jesús; Ferreira‐González, Ignacio; et al.
Abstract: Aged cardiomyocytes develop a mismatch between energy demand and supply, the severity of which determines the onset of heart failure, and become prone to undergo cell death. The FoF1‐ATP synthase is the molecular machine that provides >90% of the ATP consumed by healthy cardiomyocytes and is proposed to form the mitochondrial permeability transition pore (mPTP), an energy‐dissipating channel involved in cell death. We investigated whether aging alters FoF1‐ATP synthase self‐assembly, a fundamental biological process involved in mitochondrial cristae morphology and energy efficiency, and the functional consequences this may have. Purified heart mitochondria and cardiomyocytes from aging mice displayed an impaired dimerization of FoF1‐ATP synthase (blue native and proximity ligation assay), associated with abnormal mitochondrial cristae tip curvature (TEM). Defective dimerization did not modify the in vitro hydrolase activity of FoF1‐ATP synthase but reduced the efficiency of oxidative phosphorylation in intact mitochondria (in which membrane architecture plays a fundamental role) and increased cardiomyocytes' susceptibility to undergo energy collapse by mPTP. High throughput proteomics and fluorescence immunolabeling identified glycation of 5 subunits of FoF1‐ATP synthase as the causative mechanism of the altered dimerization. In vitro induction of FoF1‐ATP synthase glycation in H9c2 myoblasts recapitulated the age‐related defective FoF1‐ATP synthase assembly, reduced the relative contribution of oxidative phosphorylation to cell energy metabolism, and increased mPTP susceptibility. These results identify altered dimerization of FoF1‐ATP synthase secondary to enzyme glycation as a novel pathophysiological mechanism involved in mitochondrial cristae remodeling, energy deficiency, and increased vulnerability of cardiomyocytes to undergo mitochondrial failure during aging. Abstract : This study identified FoF1‐ATP synthase as a prominent target of dicarbonyl stress in cardiomyocytes during aging. Non‐enzymatic glycation of several units within FoF1‐ATP synthase holocomplex is proposed to interfere with spontaneous enzyme dimerization/oligomerization, which in turn reduces cristae curvature and energy efficiency in intact mitochondria and increases the sensitivity of cardiomyocytes to undergo pathological mitochondrial permeabilization in response to stress.